2006
DOI: 10.1002/marc.200600049
|View full text |Cite
|
Sign up to set email alerts
|

Grafting of Poly(tBA) and PtBA‐b‐PMMA onto the Surface of SWNTs Using Carbanions as the Initiator

Abstract: Summary: Soluble carbon nanotubes were prepared by treating SWNTs with sec‐butyllithium and subsequently using the generated carbanions as the initiator to graft PtBA and PtBA‐b‐PMMA onto the surface of SWNTs. The anionic polymerization initiated by SWNTs‐bearing carbanions not only provides a powerful strategy for functionalizing SWNTs but also gives us knowledge of the sidewall chemistry of SWNTs. The results indicate that a carbanion born on SWNTs behaves like an anionic initiator with high steric hindrance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…Oxidation is the most common one, for example, in an oxidizing acid (HNO 3 or H 2 SO 4 ). In such a treatment it is possible to attach oxygen and hydroxyl (OH) or carboxyl (COOH) groups to graphene [38] . When graphene is covered more or less uniformly with hydroxyl or carboxyl groups, the material is called graphene oxide, which is essentially a highly defective graphene sheet functionalized with oxygen groups [39] .…”
Section: Chemical Methodsmentioning
confidence: 99%
“…Oxidation is the most common one, for example, in an oxidizing acid (HNO 3 or H 2 SO 4 ). In such a treatment it is possible to attach oxygen and hydroxyl (OH) or carboxyl (COOH) groups to graphene [38] . When graphene is covered more or less uniformly with hydroxyl or carboxyl groups, the material is called graphene oxide, which is essentially a highly defective graphene sheet functionalized with oxygen groups [39] .…”
Section: Chemical Methodsmentioning
confidence: 99%
“…The polymerizations of vinyl groups (the most studied CCN-initiated graft-from reaction) have been shown to be a living polymerization, allowing block copolymers to be synthesized in situ. 379 These graft-from functionalized nanocarbons show contrasting properties compared to graft-to approaches, prepared by attaching monoterminated presynthesized polymers to the CCN. The graft-from approach has been shown to produce higher grafting ratios and higher solubilities for graphenides.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…Using the same approach, Chen et al [38] showed that the carbanions on the surface of SWNTs can initiate the polymerization of tert-butyl acrylate (t-BA) but not that of methyl methacrylate (MMA) (Scheme 7). The authors suggested that a possible reason for this behavior was the difference in the reactivity of the two monomers toward the delocalized carbanions on the SWNTs.…”
Section: Anionic Polymerization From Carbon Nanotubesmentioning
confidence: 95%